IDENTIFIKASI EKTOPARASIT DAN KOMPETITOR KERANG HIJAU (Perna viridis) YANG DIBUDIDAYAKAN DALAM BAGAN TANCAP DI LAUT JAWA KECAMATAN SIDAYU KABUPATEN GRESIK - Mohammad Rudy; Ummul Firmani; Farikhah Farikhah (Universitas Muhammadiyah Gresik, 2023)
The green mussel (Perna viridis) is an important commodity in marine aquaculture. A challenge in green mussel cultivation is the presence of diseases caused by parasites that attach or live on the mussels. This research aims to determine the abundance of ectoparasites and competitors on green mussels in the mentioned waters. The research methods employed both qualitative and quantitative descriptive approaches. The observed research variables included species identification, prevalence and intensity of ectoparasites, as well as diversity and abundance of competitors. The findings revealed the presence of 2 ectoparasite species and 10 competitor species. The highest prevalence of Balanus sp. was recorded in Bagan Tancap I for mussels larger than 4 cm, at 79.6%Â±6.16 (moderate), while the lowest prevalence was in Bagan Tancap II for mussels smaller than 4 cm, at 33.3%Â±1.05 (common). The highest intensity of Balanus sp. ectoparasite attacks occurred in Bagan Tancap I for mussels larger than 4 cm, at 7.18 ind/mussel (moderate), and the lowest intensity was in Bagan Tancap II for mussels smaller than 4 cm, at 1.75 ind/mussel (low). The intensity of sea snail egg infestations ranged from 1 to 2 ind/mussel, with no significant difference (P>0.05). The highest competitor abundance was found in Bagan Tancap I with the species Nereis sp., at 0.57 ind/mussel, and the highest competitor diversity was also observed in Bagan Tancap I with the species crab at 36.292 ind/mussel. Considering the prevalence and intensity values of Balanus sp. ectoparasites on green mussels in the waters of the Java Sea in Kecamatan Sidayu, it is still suitable for green mussel cultivation.